Primary signet ring carcinoma of the rectum: a rare entity - Puri, Monica; Singh, Neha; Bal, M. S.; Gupta, Neelam (International Journal of Research in Medical Sciences, 2021)
Signet ring cell carcinoma constitute an uncommon histological type of rectal cancer with less than 1% of all rectal neoplasms. It usually behaves aggressively and has an inferior prognosis. Herein, we present a rare case in young male diagnosed by trucut biopsy.